Excessive altruism - Wilson *, John (Journal of beliefs and values, 2004)
Altruism is an ideal which is almost universally approved. It is argued here that such almost universal acceptance of altruism may be grounded on a failure to interrogate the complexity both of the philosophical construct and of the human motivation underpinning its implementation.